Impact of Transparency on Public Trust in a Government Charity and Gaming Office as Mediated by Corporate Social Responsibility - Ostan, Ellyn A.; Dr. Alger P. Dura (American Journal of Public Policy and Administration, 2024)
Purpose: This study investigated the mediating role of corporate social responsibility (CSR) on the relationship between transparency and public trust in a government and charity gaming office in Davao City. Materials and Methods: Using a quantitative, mediating design, samples of 300 clients were selected using stratified sampling surveyed through standardized modified instruments. The gathered data was analyzed using Mean, Pearson r, Regression and Medgraph using Sobel z-test. The pertinent results were presented appropriately in tables. Findings: The findings revealed an overall high level of transparency within the organization. Furthermore, the results demonstrated a very high level of public trust, as well as a very high level of CSR. The test of relationship revealed significant correlation among the variables. The mediation analysis revealed that CSR significantly mediated the relationship between transparency and public trust in the organization. The relationships between the variables are all significant; therefore, there is only partial mediation of CSR on the relationship between transparency and public trust. Partial mediation suggests that not only is there a significant relationship between the mediator and the dependent variable but that there is also direct relationship between the independent and dependent variable. Implications to Theory, Practice and Policy: The study has uncovered significant implications for practice, theory, and policy regarding the relationships between transparency, public trust, and corporate social responsibility (CSR). It was found that transparency is closely linked to public trust and CSR. Specifically, a strong correlation was observed between transparency and public trust and between transparency and CSR. Additionally, a significant relationship was established between CSR and public trust. Given the overall high level of transparency observed, the researcher suggests that the PCSO branch in Davao City should maintain this level in this domain and focus on enhancing transparency across other indicators, particularly in terms of secrecy. To address this, it is recommended that the organization improve its information dissemination practices to clients. Moreover, future researchers must delve deeper into the relationships among transparency, public trust, and CSR, particularly within the context of Davao City or other regions of the country. More empirical studies on these variables need to be conducted in these specific contexts. Thus, further research could provide valuable insights for both academia and policymaking.